Influence of ideal and non-ideal excitation sources on the dynamics of a nonlinear vibro-impact system - Moraes, Fernando H. [UNESP]; Pontes, Bento R. [UNESP]; Silveira, Marcos [UNESP]; Balthazar, José M. [UNESP]; Brasil, Reyolando M.L.R.F. (My University, 2013)
The objective of the present work is to analyze the dynamics of a vibro-impact system consisting of two blocks of different mass coupled by a spring with two stages. Two different types of excitation sources for the system are used in the analysis: The first is an ideal excitation in form of a harmonic force, and the second is a non-ideal excitation in form of a DC electric motor with limited power supply which has an unbalanced rotor. The control parameter for both situations is the excitation frequency of the system. The analysis includes time histories of displacements and velocities, phase portraits and diagrams of the displacement and frequency, used to show the Sommerfeld effect. For certain values of the parameters of the system, the motion is chaotic. The mathematical model of the system is used to obtain an insight to the global dynamics of the vibro-impact system. The model with a non-ideal excitation is more realistic, complete and complex than the model with the ideal excitation.
Keywords: Limited power supply; Non-ideal excitation; Sommerfeld effect; Vibro-impact system